Análise de lesões desportivas em jogadores de futebol: prevalência e fatores associados - Silva, Jaédson Bruno Pereira da (2019)
Introduction: Soccer is the most popular sport in the world. It is one of the sports with greater risk of injuries, because it is characterized by intense physical contact, short, fast and no continuous movements, which may cause traumas. Thus, it is relevant to quantify them and to know the factors inherent to these injuries in the players for further elaboration of preventive models. Objective: Analyzing the occurrence of sports injuries in soccer players, and associate them with specific risk factors of the modality and the athlete. Method: The study is characterized as cross sectional and it weit observed 28 professional soccer players from the Associação Desportiva Confiança, in the city of Aracaju/SE. The data were collected from interviews guided by a Reference Morbidity Survey, adapted to the features of soccer, with the purpose to obtaining information about the nature of the injury, anatomical site affected, involved mechanism of action and related factors to the athlete, then statistical analysis was performed. Results: The most prevalent lesion in the analyzed sample was muscular distention; The most affected body sites were the lower limbs (mainly the thigh region); And the most injured players play in the midfield and attack positions; Running highlighted the mechanism most involved in trauma; About the factors that would hypothetically influence the number of injuries by the athletes, the item "age" was the only statistically significant (p* 0.041). Conclusion: There was no connection between the injury itself and anthropometric variables and/or training time of the players interviewed. Future research are necessary to reach a better understanding of the factors associated with the occurrence of injuries in soccer so that it can be controlled, prevented or minimized its severity.